LOW SEISMIC VELOCITY LAYERS IN THE EARTH'S CRUST BENEATH EASTERN SIBERIA (RUSSIA) AND CENTRAL MONGOLIA: RECEIVER FUNCTION DATA AND THEIR POSSIBLE GEOLOGICAL IMPLICATION - Zorin Yu.A.; Mordvinova V.V.; Turutanov E.Kh.; Belichenko B.G.; Artemyev A.A.; Kosarev G.L.; Gao S.S. (My University, 2002)
Analysis of teleseismic receiver functions at digital stations along the Bratsk–Irkutsk–Ulanbaatar–Undurshil profile suggests that low-velocity layers in the Earth's crust exist not only beneath the Baikal rift zone, where such a layer was found earlier by Deep Seismic Sounding (DSS), but also beneath Early Paleozoic Sayan–Baikal, Paleozoic Mongolian, Early Mesozoic Mongolia–Okhotsk fold areas, and beneath the Siberian platform. The reliability of detection of the low-velocity layers by receiver function analysis has been checked by numerical modeling. The results of this modeling demonstrate that receiver functions can reveal the low-velocity layers in the crust if the initial model (starting approximation) is close to real velocity distribution, and if the model medium is divided into thin layers. Averaged DSS velocity model without low-velocity layers was used as starting approximation for the inversion of observed receiver functions. The low-velocity layers are interpreted to reflect inhomogeneities of the Earth's crust formed during its evolution. Most of these layers are presumed to correspond to thick mylonite zones related to large pre-Cenozoic thrusts. The mylonites possess a great seismic anisotropy caused by the mineral orientation formed by the ductile flow in large thrust zones. They can result in low-velocity layers only for seismic waves whose rays are oriented perpendicular to the mylonite foliation, i.e., in the direction of the minimum velocity; the velocities along the foliation direction can be rather high. Therefore, the low-angle mylonite zones can be distinguished by the receiver function method, which uses the waves from the teleseismic events with nearly vertically oriented rays. The suggestion that the low-velocity layers mark low-angle thrusts is in agreement with gravity and geological data. The amount of overthrusting is estimated to be as large as several hundred kilometers. Multichannel seismic profiling can be used to verify the existence and the deep geometry of the presumed thrusts.